Social Incidence of the General Sales Tax in Pakistan - Refaqat, Saadia (IMF Working Papers; Working Paper, 2003)
This paper analyses the social incidence of the general sales tax (GST) in Pakistan. The main finding of the study is that contrary to widespread perception, the social incidence of the GST in Pakistan is slightly progressive. The main reason for this counterintuitive result is that most items heavily consumed by the poor are exempt from GST in Pakistan.